Age, sex-and what else? Rethinking priorities to close gaps in the HIV care cascade. - Jamieson,L; Rosen,S; Meyer-Rath,G; Mokhele,I; Musakwa,N; Imai-Eaton,JW; Reed,DM; Apollo,T; Uetela,DM; Shodell,D; Ehrenkranz,P; Fox,MP; et al. (J Int AIDS Soc, 2026)
INTRODUCTION: Many countries with high HIV burden have made substantial progress towards UNAIDS 95-95-95 targets and ending AIDS, but gaps in some sub-populations hinder overall achievement, even as programmes face potentially diminished resources. While certain broad groups defined by age, sex or large geographic regions are commonly labelled as "high-risk" for being out of care, most individuals within these groups are in care and virally suppressed. Characteristics beyond age and sex (e.g. behavioural, socio-economic, smaller geographic areas) may differentiate those requiring targeted intervention strategies. Our Closing The Gap project aims to characterize unreached and disengaged sub-populations for targeted HIV interventions across Mozambique, South Africa and Zimbabwe, countries selected for their varied target achievement and diverse populations. We discuss overarching themes from the first Closing The Gap workshop, convening government stakeholders, implementers, researchers and community representatives in February 2025. DISCUSSION: Key themes emerged from the workshop: (1) the importance of considering absolute sub-population size, alongside percentages, when assessing service gaps; (2) limitations of existing data and analytic paradigms beyond age-and-sex categories, highlighting the need for richer, contextual data linked to care cascade outcomes (e.g. clinical markers, mobility, socio-economic circumstances) and analyses incorporating additional factors for identifying more granular sub-populations; (3) need to identify individuals who do not require differentiated care to better prioritize resources to those not served by existing models; and (4) in the context of decreasing funding, the need to balance the cost and complexity of differentiated interventions with the feasibility and cost-effectiveness of standardized approaches, including self-selection strategies. CONCLUSIONS: It is critically important to generate more efficient strategie